Does the Ethical Culture of Organisations Promote Managers’ Occupational Well-Being? Investigating Indirect Links via Ethical Strain - Huhtala, Mari; Feldt, Taru; Lämsä, Anna-Maija; Mauno, Saija; Kinnunen, Ulla (2011)
The present study had two major aims: first, to examine the construct validity of the Finnish 58-item Corporate Ethical Virtues scale (CEV; Kaptein in J Org Behav 29:923–947, 2008) and second, to examine whether the associations between managers’ perceptions of ethical organisational culture and their occupational well-being (emotional exhaustion and work engagement) are indirectly linked by ethical strain, i.e. the tension which arises from the difference in the ethical values of the individual and the organisation he or she works for. The sample consisted of 902 managers from different organisations, in middle and upper management levels, aged 25–68 years. The results of the confirmatory factor analysis (CFA) provided support to the hypothesised eight-factor structure of the CEV scale; i.e. the scale contained the factors of clarity, congruency of supervisors, congruency of senior management, feasibility, supportability, transparency, discussability and sanctionability. In addition, it emerged from the CFAs that the high intercorrelations of these factors can be explained by the second-order factor of ethical culture. The managers’ perceptions of the ethical culture prevailing in their organisations were associated with their occupational well-being both directly (high-work engagement) and indirectly via a low level of ethical strain (low-emotional exhaustion). Thus, the findings indicated that the ethical culture of organisations plays a major role in managers’ occupational well-being.
Keywords: occupational well-being; Managerial Work; ethical strain; Ethical Culture; Corporate ethical virtues